Prosthesis-patient mismatch following transcatheter aortic valve replacement for degenerated transcatheter aortic valves: the TRANSIT-PPM international project - Testa, Luca; Casenghi, Matteo; Criscione, Enrico; Van Mieghem, Nicolas M.; Tchétché, Didier; Asgar, Anita W.; De Backer, Ole; Latib, Azeem; Reimers, Bernhard; Stefanini, Giulio; Trani, Carlo; Giannini, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: A severe prosthesis-patient mismatch (PPM) is associated with adverse outcome following transcatheter aortic valve replacement (TAVR) for de novo aortic stenosis or failed surgical bioprosthesis. The impact of severe PPM in patients undergoing TAV-in-TAVR is unknown. Aims. We sought to investigate the incidence and 1-year outcomes of different grades of PPM in patients undergoing TAV-in-TAVR. Methods: The TRANSIT-PPM is an international registry including cases of degenerated TAVR treated with a second TAVR. PPM severity as well as in-hospital, 30-day and 1-year outcomes were defined according to VARC-3 criteria. Results: Among 28 centres, 155 patients were included. Severe PPM was found in 6.5% of patients whereas moderate PPM in 14.2%. The rate of severe PPM was higher in patients who underwent TAV-in-TAVR with a second Self-Expanding suprannular (S-SE) TAVR (10%, p=0.04). Specifically, the rate of severe PPM was significantly higher among cases of a SE TAVR implanted into a balloon expandable (BE) device (19%, p=0.003). At 1-year follow-up, rate of all-cause mortality, and the rate of patients in NYHA class III/IV were significantly higher in the cohort of patients with severe PPM (p=0.016 and p=0.0001, respectively). Almost all patients with a severe PPM after the first TAVR had a failed <23 mm BE THV: the treatment with a S-SE resolved the severe PPM in the majority of the cases. Conclusion: After TAV-in-TAVR, in a fifth of the cases a moderate or severe PPM occurred. A severe PPM is associated with an increased 1-year all-cause mortality. Clinical Trial Registration. https://clinicaltrials.gov/ct2/show/NCT04500964, ClinicalTrials.gov Identifier: NCT04500964